2022
DOI: 10.11604/pamj.2022.41.202.31696
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated beverage consumption among adolescents in Sagamu, Nigeria: implications for health promotion

Abstract: Introduction the mental and physical stimulating effects of caffeine have led to an increase in consumption of caffeinated beverages. Adolescents are at an increased risk of excessive caffeine consumption and its associated adverse health consequences. This study therefore assessed the pattern of caffeinated drink consumption among in-school adolescents in Sagamu, Ogun State, Nigeria. Methods a descriptive, cross-sectional study was carried out among 350 adolescents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We have read with great interest the paper “Caffeinated beverage consumption among adolescents in Sagamu, Nigeria: implications for health promotion” by Sholeye O et al . [ 1 ] and we found it of importance with a view to health prevention in young subjects. This cross-sectional study carried out among 350 adolescents evaluated the pattern of caffeinated drink consumption among in-school adolescents in Sagamu, Ogun State, Nigeria.…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 81%
See 1 more Smart Citation
“…We have read with great interest the paper “Caffeinated beverage consumption among adolescents in Sagamu, Nigeria: implications for health promotion” by Sholeye O et al . [ 1 ] and we found it of importance with a view to health prevention in young subjects. This cross-sectional study carried out among 350 adolescents evaluated the pattern of caffeinated drink consumption among in-school adolescents in Sagamu, Ogun State, Nigeria.…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 81%
“…These aspects indicate the need for educational interventions aimed at developing adolescents' knowledge and skills related to energy drinks and their effects on health. Another interesting aspect reported by the authors [ 1 ] is that a large number of respondents reported cravings for caffeinated beverages. Food craving has been reported in several manuscript as a way to cope with stress during the last 2 years [ 5 ].…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%